A reusable surface-quaternized nanocellulose-based hybrid cryogel loaded with N-doped TiO2 for self-integrated adsorption/photo-degradation of methyl orange dye. Issue 28 (20th March 2017) - Chen, Yufei; Liu, Hongzhi; Geng, Biyao; Ru, Jing; Cheng, Chen; Zhao, Ying; Wang, Likui
Abstract : Self-integrated adsorption/photo-degradation of methyl orange dye. Abstract : In this work, an easily recyclable surface-quaternized nanofibrillated cellulose (Q-NFC)-based hybrid cryogel loaded with N-doped TiO2, was fabricated through a facile one-pot hydrothermal treatment followed by freeze-drying. Due to the web-like network structure consisting of many densely entangled nanofibrils, the Q-NFC was able to act as a "green" template for supporting N-doped TiO2 . The physicochemical characteristics and micro-structure as well as the MO adsorption/photo-degradation properties of the resultant hybrid cryogels were characterized. It was demonstrated that quaternary ammonium groups anchored onto the surfaces of a Q-NFC backbone were responsible for the modest adsorption of the N-doped hybrid cryogel toward the anionic dye, whereas doping with N species enhanced the photo-catalytic activities of loaded anatase TiO2 on MO under the irradiation of simulated solar light. Furthermore, the N-doped hybrid cryogel with mechanical durability demonstrated an excellent self-integrated removal percentage of MO (more than 99%) as well as reusability during multiple adsorption/photo-degradation cycles. Its advantages would make the cryogel an eco-friendly alternative for the harmless treatment of dye pollutants without causing a second pollution. Finally, the possible photo-degradation mechanism of MO was presented on the basis of the optical and electrochemical properties.